Impact of forest thinning on aboveground macrofungal community composition and diversity in Mediterranean pine stands. (December 2021) - Collado, E.; Bonet, J.A.; Alday, J.G.; Martínez de Aragón, J.; de-Miguel, S.
Highlights: Forest thinning caused short-term changes in macrofungal community composition. Heavy thinning caused the greatest compositional changes in the fungal community. Light thinning mainly affected particular fungal species of socioeconomic interest. Weather mediated the compositional response of the fungal community to thinning. There was no effect of forest thinning on fungal sporocarp species diversity. Abstract: Fungal communities are especially relevant in Mediterranean regions, a 'hotspot' of fungal diversity, and where the value of edible commercial sporocarps may be much higher than the income from timber products. Assessing the effects of forest management practices together with the modulating role of climate on sporocarp community composition and diversity is crucial for understanding their impacts on fungal-related ecosystem services. Yet, previous research on forest management impacts on aboveground fungal diversity and community composition is scant, sometimes contradictory and mainly focused on rather short-term impacts. We quantified the long-term response of the sporocarp community composition and diversity to different forest thinning intensities in Mediterranean Pinus pinaster forest stands, and the interactions with weather conditions in modulating the fungal response. We relied on 28 permanent plots representing a thinning intensity gradient, monitored for sporocarp diversity on a weekly basis during eleven consecutive years. Weather conditions of each plot were obtained through interpolation from different meteorological stations. Overall, the fungal sporocarp community composition showed short-term (<2 years) changes mainly under both heavy and light thinning intensities compared to unthinned plots. The unexpected compositional change caused by light thinning intensities affected only certain ectomycorrhizal fungi ( Lactarius group deliciosus ). Climatic factors, mostly the mean temperature of September and October, contributed to enhancing or diminishing the compositional response of macrofungi to forest thinning. Moreover, there was no effect of forest thinning on sporocarp species diversity (i.e., richness and evenness). Both ectomycorrhizal and saprotrophic species richness and ectomycorrhizal species evenness increased over time. Our results indicate that the post-treatment conditions following forest thinning may cause short-term successional changes in both ectomycorrhizal and saprotrophic fungal assemblages, benefiting, in turn, particular fungal species of socioeconomic interest by producing large amount of sporocarps. Furthermore, forest thinning with careful and low-impact removal of trees does not jeopardize sporocarp diversity.